Evaluation of Guidelines and Consensus on Ectopic Pregnancy Based by AGREE II Method - Fu Y; Zhang W; Wang Q; Hu C; Li Q; Huang J (Dove Medical Press, 2023)
Yiran Fu,1 Weishe Zhang,1,2 Qi Wang,1 Caihong Hu,1 Qi Li,3 Jingrui Huang1 1Department of Obstetrics, Xiangya Hospital Central South University, Changsha, People's Republic of China; 2Hunan Engineering Research Center of Early Life Development and Disease Prevention, Changsha, People's Republic of China; 3Reproductive Medicine Center, Xiangya Hospital Central South University, Changsha, People's Republic of ChinaCorrespondence: Jingrui Huang, Department of Obstetrics, Xiangya Hospital Central South University, 87 Xiangya Road, Changsha, 410008, People's Republic of China, Email jingruihuang@hotmail.com; huangjingrui@csu.edu.cnIntroduction: To evaluate the methodological quality of diagnosis and treatment guidelines/consensus related to ectopic pregnancy.Materials and methods: Use the "Appraisal of Guidelines and Research and Evaluation" (AGREE II) method to evaluate the differences among the guideline/consensus.Results: We appraised 9 clinical practice guidelines for ectopic pregnancy (9 clinical practice guidelines from 5 countries) including the United States, United Kingdom, Ireland, Canada, and China. The guidelines received the highest scores for clarity of presentation (82.72%) and lowest scores for editorial independence (30.56%). The comprehensive recommendations of the 7 guidelines were Grade B, the other 2 guidelines were Grade C.Conclusion: The overall quality of the ectopic pregnancy guidelines had room for improvement. It is recommended to supplement and improve the four fields of "independence", "rigor", "participants" and "application", especially the "independence" and "application" fields.Keywords: guidelines, ectopic pregnancy, pelvic pain, AGREE II, clinical practice